A Non-enzymatic Electrochemical Sensor for Glucose Detection Based on Ag@TiO2@ Metal-Organic Framework (ZIF-67) Nanocomposite - Arif, Dooa; Hussain, Zakir; Sohail, Manzar; Liaqat, Muhammad Arman; Khan, Muzamil Ahmad; Noor, Tayyaba (Frontiers in Chemistry, 2020)
This work presents the preparation of an efficient and sensitive glucose sensor for the detection of glucose in an alkaline media. The glucose sensor is composed of Metal Organic Framework (MOF) composite comprising Ag@TiO2 nanoparticles. The hybrid of Ag@TiO2 encapsulated in ZIF-67 was synthesized by solvothermal method and applied onto a glassy carbon electrode (GCE) for non-enzymatic sensing of glucose. The porosity of ZIF-67 was favorable for the unhindered diffusion and entrapment of glucose and its cavities served as reaction vessels. The electrochemical behavior of Ag@TiO2@ZIF-67 showed amplified results when compared with that of Ag@TiO2 and ZIF-67. Cyclic test towards the oxidation of glucose has demonstrated excellent stability of MOF based hybrid sensor. The sensor based on Ag@TiO2@ZIF-67 showed high sensitivity of 0.788 µAµM-1cm-2 with a linear concentration range of 48 µM- 1mM and a response time of 5 s with an excellent detection limit of 0.99 µM (S/N = 3).